Efektivitas Hukuman Mati sebagai Deterren dalam Kejahatan Korupsi: Studi Kasus di Negara-negara Asia - Aditya, Muhamad Ghozi; Maulidah, Khilmatin; Soliehin, Rizky Amalia; Amri, Ahmad Almaududy (Neolectura, 2024)
Corruption has become a chronic ailment troubling many countries, especially in the Asian region. Numerous nations are seeking stringent solutions to combat this crime, one of which is the implementation of the death penalty as a form of deterrence or prevention. This research aims to analyze the effectiveness of the death penalty as a preventative tool against corruption crimes in Asian countries. The research methodology employed is descriptive qualitative, utilizing a case study approach on several Asian nations that enforce the death penalty for corruption offenses. The findings suggest that even though the death penalty is considered one of the methods to reduce corruption crime rates, its effectiveness as a deterrent varies across countries, depending on factors like legal culture, legal system, and public support for the punishment. This study provides an in-depth view of the extent to which the death penalty can serve as a preventive measure against corruption crimes in Asia and offers recommendations for nations currently considering implementing or revising death penalty policies in the context of corruption offenses.